On elations in semi-transitive planes - N. L. Johnson (International Journal of Mathematics and Mathematical Sciences)
Let π be a semi-transitive translation plane of even order with reference to the subplane π0. If π admits an affine elation fixing π0 for each axis in π0 and the order of π0 is not 2 or 8, then π is a Hall plane.